Privatization Thesis and its trends in Iraq after 2003 - فتاح, عبد الجبار محمود; منير, عامر سامي (Journal of Economics and Administrative Sciences, 2018)
The concept of privatization is built on the basis of the transfer of assets and services of the public sector to the private sector this concept has appeared in the eighties of the last century whene the high oil prices took place and recession solution swept the world Which called for the freedom of the market and left the room for the private sector to take the initiatine in economic activity.         Both the IMF have   adopted this thesis in their programs of the structural adjustment in light of external and internal factors helped to Create the conditions to accept thesis that under the pretext of achieving a number of economic goals.In Iraq in spite of the dominance of the privatization concpt on the Political speaches and the Media what has been achieved on the ground is completely opposite where the public sector still dominate the economic activities spported with the oil as the main exportes. the production Services episodes despite their weakness and decreases of its efficiency have been a subsidiary of the public sector. This means that the privatization thesis has no baseis in Iraq realite and the privt sector and its relatine contripution has been mentioned only in the Political speaches without any real and tangible presence except for marginall importstrad